Development of E-worksheets Integrated Profil Pelajar Pancasila on Human Circulatory System Materials Grade XI - Dewanto, Dewanto; Oprasmani, Elfa; Nevrita, Nevrita (Journal Of Biology Education, 2024)
This study aims to develop and describe the eligibility of e-worksheets integrated Profil Pelajar Pancasila on Human Circulatory System materials grade XI in terms of the validity, practicality, and effectiveness aspects. E-worksheets developed based on the development model proposed by Thiagarajan et al. (1974) known as 4-D model, consists of define, design, develop, and disseminate. Data collected from the instrument consists of quantitative and qualitative. All data in this research will be described with descriptive approach analysis. Results showed that the validation by material expert obtained with very valid interpretation, media expert obtained with very valid interpretation, praticality by student grade XI IPA 4 at SMA Negeri 2 Tanjungpinang obtained very pratical interpretation also by 6 Biology teacher obtained very practical interpretation. Furthermore, effectiveness assesment carried out using N-gain obtained 0,629 value with very effective interpretation categorized medium. In conclusion, e-worksheets integrated Profil Pelajar Pancasila on Human Circulatory System materials grade XI stated to be very valid, practical, and effective used in Biology learning.